Single-bone versus both-bone plating of unstable paediatric both-bone forearm fractures. A randomized controlled clinical trial - Mohamed Khaled (14155944) (2022)
Purpose This clinical trial compares the functional and radiological outcomes of single-bone fixation to both-bone fixation of unstable paediatric both-bone forearm fractures. Methods This individually randomized two-group parallel clinical trial was performed following the Consolidated Standards of Reporting Trials (CONSORT) statement at a single academic tertiary medical centre with an established paediatric orthopaedics unit. All children aged between nine and 15 years who presented to the emergency department at Assiut university with unstable diaphyseal, both-bone forearm fractures requiring surgical intervention between November 1, 2018, and February 28, 2020, were screened for eligibility against the inclusion and exclusion criteria. Inclusion criteria were diaphyseal unstable fractures defined as shaft fractures between the distal and proximal metaphyses with an angulation of > 10°, and/or malrotation of > 30°, and/or displacement > 10 mm after attempted closed reduction. Exclusion criteria included open fractures, Galeazzi fractures, Monteggia fractures, radial head fractures, and associated neurovascular injuries. Patients who met the inclusion criteria were randomized to either the single-bone fixation group (intervention) or the both-bone fixation group (control). Primary outcomes were forearm range of motion and fracture union, while secondary outcomes were forearm function (price criteria), radius re-angulation, wrist and elbow range of motion, and surgical time Results A total of 50 children were included. Out of these 50 children, 25 were randomized to either arm of the study. All children in either group received the treatment assigned by randomization. Fifty (100%) children were available for final follow-up at six months post-operatively. The mean age of single-bone and both-bone fixation groups was 11.48 ± 1.93 and 13 ± 1.75 years, respectively, with a statistically significant difference (p = 0.006). There were no statistically significant differences in gender, laterality, affection of the dominant hand, or mode of trauma between single-bone and both-bone fixation groups. All patients in both groups achieved fracture union. There mean radius re-angulation of the single-bone fixation groups was 5.36 ± 4.39 (0–20) degrees, while there was no radius re-angulation in the both-bone fixation group, with a statistically significant difference (p < 0.001). The time to union in the single-bone group was 6.28 ± 1.51 weeks, while the time to union in the both-bone fixation group was 6.64 ± 1.75 weeks, with no statistically significant difference (p = 0.44). There were no infections or refractures in either group. In the single-bone fixation group, 24 (96%) patients have regained their full forearm ROM (loss of ROM < 15°), while only one (4%) patient lost between 15 and 30° of ROM. In the both-bone fixation group, 23 (92%) patients have regained their full forearm ROM (loss of ROM < 15°), while only two (8%) patients lost between 15 and 30° of ROM. There was no statistically significant difference between groups in loss of forearm ROM (p = 0.55). All patients in both groups regained full ROM of their elbow and wrist joints. On price grading, 24 (96%) and 23 (92%) patients who underwent single bone fixation and both-bone fixation scored excellent, respectively. Only one (4%) patient in the single-bone fixation group and two (8%) patients in the both-bone fixation group scored good, with no statistically significant difference in price score between groups (p = 0.49). The majority of the patients from both groups had no pain on the numerical pain scale; 22 (88%) patients in the single-bone fixation group and 21 (84%) patients in the both-bone fixation groups, with no statistically significant difference between groups (p = 0.38). The single-bone fixation group had a significantly shorter mean operative time in comparison to both-bones plating (43.60 ± 6.21 vs. 88.60 ± 10.56 (min); p < 0.001). Conclusion Single-bone ulna open reduction and plate fixation and casting are safe and had a significantly shorter operative time than both-bone fixation. However, single-bone ORIF had a higher risk radius re-angulation, alas clinically acceptable. Both groups had equally excellent functional outcomes, forearm ROM, and union rates with no complications or refractures. Long-term studies are required. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00264-021-05097-z